CT- based volumetric assessment of rotator cuff muscle in shoulder arthroplasty preoperative planning. (2021) - Werthel, J- D.; Casson, F. Boux de; Burdin, V.; Athwal, G. S.; Favard, L.; Chaoui, J.; Walch, G.
No abstract available